2024
DOI: 10.1007/s10916-024-02056-0
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Five Different Artificial Intelligence Chatbots to the Top Searched Queries About Erectile Dysfunction: A Comparative Analysis

Mehmet Fatih Şahin,
Hüseyin Ateş,
Anıl Keleş
et al.

Abstract: The aim of the study is to evaluate and compare the quality and readability of responses generated by five different artificial intelligence (AI) chatbots—ChatGPT, Bard, Bing, Ernie, and Copilot—to the top searched queries of erectile dysfunction (ED). Google Trends was used to identify ED-related relevant phrases. Each AI chatbot received a specific sequence of 25 frequently searched terms as input. Responses were evaluated using DISCERN, Ensuring Quality Information for Patients (EQIP), and Flesch-Kincaid Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Temel et al reported that content created by chatGPT regarding spinal cord injury had substantial difficulties with quality 6 . Şahin et al compared 5 different AI chatbots about erectile dysfunction and found that none of the chatbots had the required level of readability and quality25 . Similar to all this research, our study also demonstrated that content about DED created by ChatGPT has significant quality issues.…”
mentioning
confidence: 99%
“…Temel et al reported that content created by chatGPT regarding spinal cord injury had substantial difficulties with quality 6 . Şahin et al compared 5 different AI chatbots about erectile dysfunction and found that none of the chatbots had the required level of readability and quality25 . Similar to all this research, our study also demonstrated that content about DED created by ChatGPT has significant quality issues.…”
mentioning
confidence: 99%
“…In the ‘Materials and Methods’ section, the authors detail their analysis of these responses using various readability scales, including DISCERN, Ensuring Quality Information for Patients (EQIP), and the Flesch-Kincaid Grade Level (FKGL) and Reading Ease (FKRE). Additionally, they disclose the names of the five AI-based chatbots used to generate the responses under analysis [ 1 ].…”
mentioning
confidence: 99%